Open-Circuit Fault Diagnosis and Fault-Tolerant Operation of Dual Inverter for Open-End Winding Interior Permanent Magnet Synchronous Motor - Lee, Hyung Woo; Lee, Kyo Beum (SCEMS 2022 - 2022 IEEE 5th Student Conference on Electric Machines and Systems, 2022)
This paper proposes the open-circuit fault diagnosis and fault-tolerant method of dual inverter with two isolated DC power sources for driving open-end winding permanent magnet synchronous motor (OEW-IPMSM). Since the multi-level effect of the topology, two-level dual inverter (TLDI) has an advantage in that fault-tolerant control which is not allowable in two-level single inverter. From the structural characteristics of TLDI, when an open fault occurs in single switch, there are switch pairs with the identical tendency of the inverter output current. In this paper, the open-circuit fault diagnosis and fault-tolerant method of TLDI is proposed. The proposed method specifies a pair of fault switches through analysis of the output current. In addition, through the single inverter mode operation using the zero-voltage vector, the switch in which open fault has occurred among the fault switch pair is detected and the tolerant control is performed immediately. The effectiveness of proposed method is verified by simulation results.
Keywords: Dual inverters; Fault-tolerant method; Faults diagnosis; Faults tolerant controls; Open faults; Open-circuit fault; Open-end winding IPMSM; Open-end windings; Single inverters; Two-level dual inverte; fault-tolerant control; open-circuit fault; open-end winding IPMSM; Two-level dual inverter